(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2009)
The stem bark of Anacardium occidentale L. (Anacardiaceae), commonly called cashew, is used in Brazilian traditional medicine for the treatment of gastric and inflammatory disorders. The present study was carried out to investigate the in vivo anti-inflammatory activities of the acetone extract (AE) of the stem bark of A. occidentale. We evaluated the pharmacological activities of this plant material through the analgesic, antiedematogenic and chemotaxic inhibitory effects produced by the AE. The oral administration (p.o.) of mice with the AE (0.1, 0.3 and 1.0 g/kg) or positive control indomethacin (10 mg/kg) inhibited acetic acid-induced writhing by 18.9, 35.9, 62.9 and 68.9%, respectively (ID50% = 530 mg/kg). The highest dose of the AE was able to inhibit croton oil-induced ear edema formation by 56.8% (indomethacin at 10 mg/kg, p.o. - 57.6% inhibition). When submitted to the carrageenan-induced peritonitis test, the AE (0.1, 0.3 and 1.0 g/kg, p.o.) impaired leukocyte migration into the peritoneal cavity by 24.8, 40.5 and 49.6%, respectively. The positive control, dexamethasone (2 mg/kg, s.c.), inhibited leukocyte migration by 66.9%. These results indicate the presence of anti-inflammatory and antinociceptive principles in the acetone extract of Anacardium occidentale, and reinforce the plant's potential therapeutic use against pain and inflammatory diseases.